2021
DOI: 10.1159/000516899
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Microenvironment Predicts the Survival of the Patients with Hepatocellular Carcinoma Treated with Anti-PD-1 Antibody

Abstract: <b><i>Introduction:</i></b> Although immune checkpoint inhibitors (ICIs) have been considered as promising agents for the treatment of advanced hepatocellular carcinoma (HCC), previous clinical trials revealed that the response to anti-programmed cell death protein 1 (anti-PD-1) monotherapy was as low as 20%. Identifying subgroups that respond well to ICIs is clinically important. Here, we studied the prognostic factors for anti-PD-1 antibody treatment based on the molecular and immunol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 52 publications
1
51
0
Order By: Relevance
“…Regarding other liquid biopsy biomarkers for the efficacy of immunotherapy, genetic alterations affect the immune cell infiltration pattern and thus might affect the efficacy of immunotherapy [ 27 ]. The WNT/CTNNB1 signaling pathway was recently reported to suppress immune cell infiltration [ 28 , 29 ], and this signaling activation in the tumor site was negatively associated with ICI treatment in HCC [ 30 ]. In the present study, we analyzed the plasma levels of DKK1, which is an antagonist of WNT signaling, as a potential surrogate marker of WNT/CTNNB1 signaling activity, but they were not associated with the response to Atezo/Bev therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding other liquid biopsy biomarkers for the efficacy of immunotherapy, genetic alterations affect the immune cell infiltration pattern and thus might affect the efficacy of immunotherapy [ 27 ]. The WNT/CTNNB1 signaling pathway was recently reported to suppress immune cell infiltration [ 28 , 29 ], and this signaling activation in the tumor site was negatively associated with ICI treatment in HCC [ 30 ]. In the present study, we analyzed the plasma levels of DKK1, which is an antagonist of WNT signaling, as a potential surrogate marker of WNT/CTNNB1 signaling activity, but they were not associated with the response to Atezo/Bev therapy.…”
Section: Discussionmentioning
confidence: 99%
“…High expression of PD-L1 may lead to the suppression of immune function ( Topalian et al, 2016 ; Li et al, 2019 ). However, clinical studies have shown that patients with increased CD8 + T cell infiltration and high PD-L1 positivity in HCC are more sensitive to anti-PD1 therapy and have a significantly improved disease control rate, which is significantly associated with prolonged PFS and OS ( Aguiar et al, 2018 ; Han et al, 2019 ; Morita et al, 2021 ). The combination of VS4718 and an anti-PD1 antibody can not only increase the infiltration of CD8 + T cells and reduce the infiltration of immunosuppressive Tregs and macrophages but also block the binding of PD1 on the surface of T cells to PD-L1 on the surface of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Immunotherapy may have completely opposite effects in these two distinct subclasses with CTNNB1 mutations. In other words, the immune-like subclass with the phenotype characterized by prominent infiltration of immune cells (e.g., infiltrations of CD8+ T cells, increases in M1 macrophages, and IFN-γ signature), and the immune-excluded subclass with the completely opposite phenotype will respond to immunotherapy very differently [16].…”
Section: Dual Aspect Of the Wnt/β-catenin Mutation (Ctnnb1 Mutation)mentioning
confidence: 99%